2D lanthanide coordination polymers constructed from a semi-rigid tricarboxylic acid ligand: crystal structure, luminescence sensing and color tuning. Issue 37 (3rd September 2020) - Liang, Guang-Ming; Wang, Shuang; Xu, Mei-yu; Chen, Hai-Lin; Liang, Guang-Yuan; Gui, Liu-Cheng; Wang, Xiu-Jian
Abstract : Three lanthanide polymers {[Ln(TMCA)(DEF)(H2 O)]·(CH3 CN)} n (Ln = Eu 1 ; Tb 2 ; Gd 3 ; H3 TMCA = 4′, 4′, 4′-[(trimethylamino)]-tris[(1, 1′-biphenyl)-2-carboxylic acid]) were synthesized under solvothermal conditions. Abstract : Three lanthanide polymers {[Ln(TMCA)(DEF)(H2 O)]·(CH3 CN)} n (Ln = Eu 1 ; Tb 2 ; Gd 3 ; H3 TMCA = 4′, 4′, 4′-[(trimethylamino)]-tris[(1, 1′-biphenyl)-2-carboxylic acid]) were synthesized under solvothermal conditions. The coordination polymers were characterized by elemental analysis, IR spectroscopy, thermogravimetric analysis and single-crystal X-ray diffraction. Single crystal X-ray diffraction analyses showed that the complexes 1, 2 and 3 are isostructural 2D coordination networks with a point symbol of {4 4 ·6 2 }. Complexes 1 and 2 exhibit red and green emission, assigned to the 5 D0 → 7 F J ( J = 0–4) transitions of the Eu 3+ ion and 5 D4 → 7 F J ( J = 6–2) transitions of the Tb 3+ ion, respectively. The luminescence explorations reveal that the Eu-MOF possesses favorable selectivity and sensitivity for testing Fe 3+ in CH3 OH solutions. Additionally, color tuning was easily achieved by varying the europium : terbium metal ratios in the reaction mixtures.